Lesional Accumulation of CD163-Expressing Cells in the Gut of Patients with Inflammatory Bowel Disease - Franzè, Eleonora (Public Library of Science, 2013)
Monocytes/macrophages displaying different markers of activation/differentiation infiltrate the inflamed gut of patients with inflammatory bowel diseases (IBD), but the role that each monocyte/macrophage subpopulation plays in the pathogenesis of IBD is not fully understood. The hemoglobin scavenger receptor CD163, a specific marker of monocytes/macrophages, has been associated with either anti-inflammatory or inflammatory functions of macrophages in several pathologies. In this study we examined the tissue distribution and function of CD163-expressing monocytes/macrophages in IBD. CD163 RNA and protein expression was more pronounced in IBD in comparison to normal controls, with no significant difference between Crohn's disease and Ulcerative colitis. In IBD, over-expression of CD163 was restricted to areas with active inflammation and not influenced by current therapy. Immunohistochemical analysis confirmed the accumulation of CD163-expressing cells in IBD, mostly around and inside blood vessels, thus suggesting that these cells are partly recruited from the systemic circulation. Indeed, FACS analysis of circulating mononuclear cells showed that the fractions of CD163-positive monocytes were increased in IBD patients as compared to controls. Functionally, interleukin-6 up-regulated CD163 expression in lamina propria mononuclear cells and mucosal explants of normal subjects. In IBD blood and mucosal cell cultures, cross-linking of CD163 with a specific monoclonal anti-CD163 antibody enhanced tumor necrosis factor-α synthesis. These findings indicate that IBD mucosa is abundantly infiltrated with CD163-positive cells, which could contribute to amplify the inflammatory cytokine response.